The Innate Cellular Immune Response in Xenotransplantation - Maeda, Akira; Kogata, Shuhei; Toyama, Chiyoshi; Lo, Pei-Chi; Okamatsu, Chizu; Yamamoto, Riho; Masahata, Kazunori; Kamiyama, Masafumi; Eguchi, Hiroshi; Watanabe, Masahito; Nagashima, Hiroshi; Okuyama, Hiroomi; et al. (Frontiers in Immunology, 2022)
Xenotransplantation is very attractive strategy for addressing the shortage of donors. While hyper acute rejection (HAR) caused by natural antibodies and complement has been well defined, this is not the case for innate cellular xenogeneic rejection. An increasing body of evidence suggests that innate cellular immune responses contribute to xenogeneic rejection. Various molecular incompatibilities between receptors and their ligands across different species typically have an impact on graft outcome. NK cells are activated by direct interaction as wells as by antigen dependent cellular cytotoxicity (ADCC) mechanisms. Macrophages are activated through various mechanisms in xenogeneic conditions. Macrophages recognize CD47 as a “marker of self” through binding to SIRPα. A number of studies have shown that incompatibility of porcine CD47 against human SIRPα contributes to the rejection of xenogeneic target cells by macrophages. Neutrophils are an early responder cell that infiltrates xenogeneic grafts. It has also been reported that neutrophil extracellular traps (NETs) activate macrophages as damage-associated pattern molecule (DAMPs). In this review, we summarize recent insights into innate cellular xenogeneic rejection.